Active Learning Training for Mathematics Teachers at Madrasah Tsanawiyah in Samarinda City: Pelatihan Pembelajaran Aktif bagi Guru Matematika Madrasah Tsanawiyah di Kota Samarinda - Firnanda Pradana Putra; Ahmad Maulana Syafii; Abdul Razak; Toni, Toni (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Active learning training for madrasah tsanawiyah mathematics teachers throughout Samarinda City was carried out with the aim of enabling teachers to develop active learning scenarios and understand the elements of an independent curriculum such as differentiated learning, numeracy literacy, and media creation using the Geogebra application. This service approach uses PAR because the Madrasah Tsanawiyah Mathematics MGMP has minimal activities and limited budget. The results of this service show that the participants who took part in the training were 21 mathematics teachers from 16 Madrasah Tsanawiyah based on the willingness of the teachers to fill out the form which was distributed via Google Form. After being given training and assistance, teachers can develop active learning scenarios in lesson implementation plans, develop numeracy literacy assessment instruments, and create learning media with the Geogebra application to be used for teaching in class. Other results show that learning in class makes students more active and students' mathematics learning outcomes increase.